SYMBOLIC CONVERGENCE OF RESTORATION AND FANTASY THEMES IN STRENGTHENING THE NASDEM PARTY’S BRAND IDENTITY - Niko Yehezkiel; Mirza Ronda; Hifni Alifahmi (Bajang Institute, 2026)
The National Democratic Party (NasDem) emerged by promoting the “Restoration of Indonesia” movement, an idea intended to revive the spirit of nationalism as envisioned in the 1945 Proclamation of Independence. The slogan “Restoration of Indonesia” distinguishes NasDem from other political parties; however, more than a decade later, tangible improvements in national and political conditions remain limited. The restoration concept has not been fully institutionalized within the party’s internal structure, creating a gap between political discourse and practical implementation. This study examines how NasDem’s symbolic cues communicate the idea of restoration, the fantasy themes that emerge in this communication, and how symbolic convergence occurs between party elites and constituents. It also analyzes the extent to which a communication model based on symbolic convergence and fantasy themes strengthens party brand identity. Grounded in Symbolic Convergence Theory (SCT) and Fantasy Theme Analysis (FTA) developed by Ernest G. Bormann, and reinforced by Kevin Lane Keller’s branding theory, this research adopts a post-positivist paradigm with a qualitative explanatory approach. Data were collected through online literature review, observation, expert interviews, and focus group discussions. The findings show that fantasy themes and symbolic cues are strategically used to communicate the “Restoration of Indonesia” narrative. Symbolic convergence occurs through restorative communication mechanisms aimed at building shared understanding between party elites and constituents. This communication model contributes significantly to strengthening brand identity. However, the study also reveals that inconsistencies between fantasy narratives and internal political practices may undermine the credibility and sustainability of the party’s brand identity